A Man of Destiny - Ifoegbuna, Ifeanyi (Literamed Publications Ltd, 2001)
This is the story of oppression and corruption of power. Obi Ikediegwu's reign of terror will not have been possible without the help of his warriors and Mmaelie, the old witch. Emeli's special talent in music wins him the heart of the princess, the only daughter of Obi Ikediegwu. Mmaelie's plots to destroy Bundu, the chief of warriors, and Emeli the enchanting musician, due to their rising fame, lead to the final blunder that gives rise to a coup plot which claims her life and that of Obi Ikediegwu at the hands of Bundu the great...
Keywords: Fairytales